The impact of corticosteroid use during anti-PD1 treatment. (June 2020) - Pan, Eva Y; Merl, Man Yee; Lin, Katherine
Background: The advent of anti-PD1 therapy for cancer treatment has led to improvements in response rates and overall survival. However, anti-PD1 therapy has the potential to cause immune-related adverse events (irAEs), which can be treated with corticosteroids if severe. The clinical implications of concomitant immunotherapy and systemic steroids remain unclear, as short courses of steroids do not significantly suppress T-cell function. The primary objective of this study is to determine if the use of concomitant steroids impacts the efficacy of anti-PD1 therapy. Methods: This retrospective, single-center study reviewed adult patients who received at least four cycles of nivolumab or pembrolizumab for the treatment of melanoma, non-small cell lung cancer (NSCLC), or renal cell carcinoma from November 2014 to February 2016. Patients who received steroids (prednisone equivalent >10 mg) during anti-PD1 therapy were divided into two main cohorts based on the duration of steroid administration of ≤2 weeks or >2 weeks. Time to disease progression, overall response, and overall survival were assessed. Results: Twenty-seven of 55 patients (13 melanoma, 11 NSCLC, 3 renal cell carcinoma) required steroids during anti-PD1 therapy. In patients who received steroids, median time to disease progression was 5.6 months for melanoma, 5.8 for NSCLC, and 2.0 for renal cell carcinoma. The overall response rate (ORR) was 3/13 (23%) for melanoma, 6/11 (54%) for NSCLC, and 1/3 (33%) for renal cell carcinoma. Median overall survival was 11.9 months for melanoma, 9.9 for NSCLC, and not reached for renal cell carcinoma. Thirteen patients who had received steroids expired; 11 of these patients had received prednisone >10 mg/day for >2 weeks. Conclusion: High-dose steroids for long durations during anti-PD1 therapy may be associated with poorer survival outcomes.